Changing Attitudes Toward Information Management: They Just Don't Seem to Get It - Bent, Dale (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Information Management (IM) is an important activity in many organizations. However, it is relatively recently that the principles of IM have been sufficiently clear, and the technology of information processes sufficiently developed, to consider the rigorous organization-wide application of IM principles. Reported field experience is as yet scarce on the degree of acceptance of IM principles by management and the results of the implementation. A large-scale longitudinal international survey of senior managers in a wide variety of organizations is planned.